Balance or Highlight? The Impact of Power on Consumer Choices for Joint Consumption - Chaeyeong Kim (Asia Marketing Journal)
Consumers often make decisions on behalf of the self and others, such as family, friends, or colleagues, when choosing products to jointly consume. Postulating that power—a central element of social dynamics—shapes reliance on internal versus external information, the current research explores its effect on joint consumption choices. Across three studies, I find that low-power individuals balance self and others’ preferences, whereas high-power individuals are likely to highlight their preferences (H1). In addition, I provide evidence for decision-making strategy (i.e., reliance on reasons vs. feelings) as the key mechanism underpinning the relationship between power and joint consumption choices (H2). Finally, I demonstrate that this effect is attenuated when individuals have a heightened need for justification, via moderation and mediation (H3 and H4).